High temperature negative mass plasma - Golovkin, BG (Annals of Mathematics and Physics, 2024)
A review of studies of matter with negative mass - negamatter, consisting of negaparticles - is given. Based on the assumption that Newton’s laws are valid for negaparticles, their behavior in relation to other particles is described. It has been discovered that high-temperature plasma is a negasubstance, but only such a plasma whose temperature is above a certain critical temperature, depending on the chemical composition of the original substance, can be calculated using the appropriate formula. In addition, if anybody is in a state of motion with a speed above 235696.8871 km/s, then its substance undergoes a phase transition and becomes negamatter.